Role of exopolysacharide bacteria in improving the tolerance of Zea mays (L.) Seedlings to drought stress - Karrar . K . Hashim; Khalid A. Hussein; Najeh H. Kadhum (Journal of Kerbala for Agricultural Sciences, 2024)
In this study, 20 Bacillus and 20 Pseudomonas bacteria were isolated from arid and semiarid soil samples. Bacillus and Pseudomonas bacteria are soil-dwelling bacteria that can promote plant growth. They are known to produce exopolysaccharides (EPS), which can help plants retain water and tolerate drought stress. The isolates were morphologically and microscopically characterized and tested for their ability to produce exopolysaccharides. The isolates that were most capable of producing exopolysaccharides were used as biofertilizer to improve drought tolerance of maize seedlings. The seedlings were irrigated every 24, 48, or 72 h. The results showed that biofertilizers containing the most EPS-producing Bacillus and Pseudomonas isolates, B. subtillus, B. brevibacillus, P. putida, P. fluorescens, significantly improved the transpiration rate, stress tolerance index, drought tolerance, chlorophyll stability and membrane damage index of maize seedlings.